Efficacy of Ayurvedic Formulations in Dyslipidemia (Medo Dusti) (AYUSHDHARA, 2023)
Obesity (Overweight) is the condition arises as consequence of various metabolic disorder in which dyslipidemia is one of them. Dyslipidemia is described by an increase in Total Cholesterol, low density lipoprotein (LDL), triglycerides (TGA’s) concentration in the blood. In Ayurvedic classics it had been described as Medoroga in which excessive deposition of Meda Dhatu in body produces various symptoms. In the above case report patient comes with symptoms of Meda dusti and diagnosed on the basis of deranged lipid profile. The combination of Arogyavardhini vati, Navak guggul with Anupaan of Darvyadi Kwath was prescribed. After 34 days of drug intervention with scheduled diet plan there is a significant reduction in Triglycerides, Cholesterol and other parameters lies in the normal range, weight reduces (from 71kg to 68kg) within 30 days with BMI. The management of the disease results in formation of vitiated Kapha and meda dhatu through Dravya's of Lekhaniya Gana with Pathya sevan.